Determining the Decision-Making Style of Online Buyers (Case Study: Kowsar Isfahan Store) - Rezaei Kojani, Mohsen; Ghafari Ashtiani, Payman; Sadeh, Ehsan; Ghorban Hosseini , Masoud (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study aimed to evaluate the decision-making styles of Sproles and Kendall among online buyers of the Kowsar Isfahan store. The main question of this research was to determine the priority and importance of Sproles and Kendall decision-making styles among the online buyers of this store.Methodology: The primary tool for data collection was electronic questionnaires on the internet with 35 items, designed and distributed based on a 7-point Likert scale, and data were collected accordingly. The statistical sample of this research included 251 individuals from the statistical community. In the data analysis phase, confirmatory factor analysis was used to extract latent variables.Findings: According to the results of this research, the online buying decision process involves six styles: perfectionism and sensitivity to quality, sensitivity to brand name, sensitivity to fashion, hedonism, confusion due to many options, and habitualness.Conclusion:  Among these styles, the decision-making style of perfectionism and sensitivity to quality was the dominant decision-making style of online buyers at the Kowsar Isfahan store.